Negative Correlation Between Serum Levels of Homocysteine and Apolipoprotein M - Wei, J.; Yu, Y.; Feng, Y.; Zhang, J.; Jiang, Q.; Zheng, L.; Zhang, X.; Xu, N.; Luo, G. (Current Molecular Medicine, 2019)
Background: Homocysteine (Hcy) has been suggested as an independent risk factor for atherosclerosis. Apolipoprotein M (apoM) is a constituent of the HDL particles. The goal of this study was to examine the serum levels of homocysteine and apoM and to determine whether homocysteine influences apoM synthesis. Methods: Serum levels of apoM and Hcy in 17 hyperhomocysteinemia (HHcy) patients and 19 controls were measured and their correlations were analyzed. Different concentrations of homocysteine (Hcy) and LY294002, a specific phosphoinositide 3- kinase (PI3K) inhibitor, were used to treat HepG2 cells. The mRNA levels were determined by RT-PCR and the apoM protein mass was measured by western blot. Results: We found that decreased serum apoM levels corresponded with serum HDL levels in HHcy patients, while the serum apoM levels showed a statistically significant negative correlation with the serum Hcy levels. Moreover, apoM mRNA and protein levels were significantly decreased after the administration of Hcy in HepG2 cells, and this effect could be abolished by addition of LY294002. Conclusions: Present study demonstrates that Hcy downregulates the expression of apoM by mechanisms involving the PI3K signal pathway.
Keywords: lipid metabolism